2021
DOI: 10.3389/fimmu.2021.804408
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase Regulates the Epigenetic Modification of Core Histones in Mast Cell Leukemia Cells

Abstract: Mast cells are immune cells that store large amounts of mast cell-restricted proteases in their secretory granules, including tryptase, chymase and carboxypeptidase A3. In mouse mast cells, it has been shown that tryptase, in addition to its canonical location in secretory granules, can be found in the nuclear compartment where it can impact on core histones. Here we asked whether tryptase can execute core histone processing in human mast cell leukemia cells, and whether tryptase thereby can affect the epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…In some cases, the directed secretion of CPA3 towards the nuclear structures of other cells becomes apparent (Figure 4g-l). The study of CPA3 in this aspect seems to be of particular interest after the discovery of the ability of tryptase to have regulatory effects on nuclear histones and thereby influence the proliferative activity of cells [120][121][122]. Moreover, there is clear immunohistochemical evidence of tryptase and CPA3 co-localization in the case of directed secretion of proteases to the nuclei of other cells (Figure 3a).…”
Section: Mechanisms Of Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the directed secretion of CPA3 towards the nuclear structures of other cells becomes apparent (Figure 4g-l). The study of CPA3 in this aspect seems to be of particular interest after the discovery of the ability of tryptase to have regulatory effects on nuclear histones and thereby influence the proliferative activity of cells [120][121][122]. Moreover, there is clear immunohistochemical evidence of tryptase and CPA3 co-localization in the case of directed secretion of proteases to the nuclei of other cells (Figure 3a).…”
Section: Mechanisms Of Secretionmentioning
confidence: 99%
“…Tryptase has recently been shown to have epigenetic effects due to its influence on the state of nuclear histones and DNA stabilization [120][121][122]. The close co-localization of CPA3 with tryptase leads to some interest in the extent to which exopeptidase is involved in these effects (Figure 3a).…”
Section: Biological Effectsmentioning
confidence: 99%
“…The other HDACi that were tested, TSA and SAHA, appeared to have the same effect, although only the TSA increase in histamine content was statistically significant. A recent study by Alanazi et al has shown that when HMC-1 are induced to undergo apoptosis by HDACi (LLME, staurosporine, UNC-0,638 and UNC-1999), tryptase is released and cleaves histones 3 and 2B, leading to increased proliferation (67). Viability in the Alanazi et al study was measured using a resazurin-based assay which measures cell metabolic activity similar to the XTT assay used in our analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The results of recent studies that have investigated the fundamental significance of tryptase entry into the nuclei of other cells [ 50 ] are supported by our findings, evidencing the potential, significant morphogenetic effects of MCs on the ovarian stroma. In particular, nuclear tryptase can process the core histones in the N-terminal tail, and thereby regulate transcription processes [ 51 , 52 ]. The provided principle of regulating the epigenetic modification of core histones, which ultimately leads to the restriction of cell proliferation, represents a strategically novel understanding of the biological function of human MC tryptase [ 52 ].…”
Section: Discussionmentioning
confidence: 99%